(untitled) (Hekima Review, 2022)
Centred on a well-defined space, in this case 19th century England, under German epistemological influence, more precisely Hegelian and Feurebarchian, and in line with the French revolution, Karl Marx’s analyses prove even more true today all over the world. Indeed, we are at the apotheosis of the absolute triumph of the commodity for which Christic teaching is a fundamental inversion. The beatitudes invite us to fight, not to improve our servitude, but to rediscover the generic being of our first ancestry and our primordial Genos.